PENGARUH KOMPENSASI, PENGALAMAN DAN PENDIDIKAN TERHADAP PRESTASI KERJA PEGAWAI DINAS PERTANIAN TANAMAN KABUPATEN OKU - Choiriyah, Choiriyah (Universitas muhammadiyah palembang, 2012)
This Research test the Influence of Compensation, Job Experience, and Education To The Job achievement on Departement of Agriculture’s Food Crop and Horticulture of Ogan Komering Ulu’s District Government. Population in this research as much 62 Officer on Departement of Agriculture’s Food Crop and Horticulture of Ogan Komering Ulu’s District Government. From calculation result by using program of SPSS for Windows Version 16.00, got result that : 1) There is influence Compensation, Job Experience, and Education which significant, by together to Job Achievement and 2) There is influence Compensation, Job Experience, and Education which significant, by partial to Job Achievement. Implementation, become the input for Departement of Agriculture’s Food Crop and Horticulture of Ogan Komering Ulu’s District Government, to paying attention Compensation, Job Experience and Education, in order to improving Job Achievement.